Perancangan Dan Pengembangan Website Covid Care Di Jember - Priza Pandunata; Bayu Taruna Widjaja Putra; Candra Bumi; Aditya Kurniawan; Oktalia Juwita (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2021)
Lots of information that is spread in the community about Covid1-19 needs to be confirmed so as not to disturb the public. Many people have not been able to distinguish between true and false information. There are still many people in Jember who have not received accurate and reliable information about the current Covid vaccine. It's not just about how to get vaccinated, but the requirements that must be met in order to get vaccinated in Jember, also have not been conveyed properly to the public. In view of this, we need a means that can facilitate the dissemination of such information properly. This service activity resulted in a website with the name CovidCare. CovidCare provides information to assist the University of Jember's covid task force in collecting data on UNEJ residents who have been vaccinated and also exposed to Covid. The CovidCare website can also make it easier for the Covid task force to accept students who want to register as Covid volunteers who are part of the Thematic KKN at UNEJ. In addition to these internal parties, the CovidCare website can also be used by outside parties (health workers) in registering the Covid vaccine.